2021
DOI: 10.1038/s41598-021-03845-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of carbon source on cell growth and the production of bioactive compounds in cell suspensions of Hancornia speciosa Gomes

Abstract: Belonging to the Brazilian flora, the species Hancornia speciosa (Gomes), known as mangabeira, has bioactive compounds of interest, such as flavonoids, xanthones, and proanthocyanidins. The objective of this study was to determine how the supplementation of sugars in culture medium affects the osmotic potential of the medium, as well as its influence on cell growth and on the concentration of phenolic compounds. For this purpose, after 90 days of subculture, 20 mL aliquots of the cultures were added to flasks … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Numerous primary and secondary metabolites, such as products of the glyoxylate pathway, anthocyanin and artemisin, have responded differently to sugars ( Arsenault et al., 2010 ). In other species, such as the Brazilian Hancornia speciosa (Gomes) cell suspension cultures, adding 3% glucose increased fresh weight and production of polyphenols ( Dantas et al., 2021 ). The differences seen in the period for achieving the maximum growth during the growth curve between Amer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous primary and secondary metabolites, such as products of the glyoxylate pathway, anthocyanin and artemisin, have responded differently to sugars ( Arsenault et al., 2010 ). In other species, such as the Brazilian Hancornia speciosa (Gomes) cell suspension cultures, adding 3% glucose increased fresh weight and production of polyphenols ( Dantas et al., 2021 ). The differences seen in the period for achieving the maximum growth during the growth curve between Amer et al.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, higher sucrose concentrations resulted in an osmotic pressure affecting cell growth. In Hancornia speciosa, it was observed that the biomass and accumulation of desirable secondary metabolites were favored by a 3% ( w/v ) sucrose concentration [ 38 ]. In the tested tamarillo ICL, there was not a decline in cell growth with 3% sucrose ( w/v ), just a slow growth compared to the cultures grown with 9% sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…However, cell lines of only a few species are capable of utilizing sugar alcohols for growth supply. Usually, the growth rate of cultures using mannitol as a substrate is reduced compared to ones with sucrose or glucose [ 84 , 125 , 126 ]. Nevertheless, Apium graveolens cultures grow on medium with mannitol as quickly as with sucrose [ 127 ].…”
Section: Organic Substratesmentioning
confidence: 99%
“…The metabolism of oligo- and polysaccharides leads to the formation of hexoses, the most common of which are fructose and glucose. Therefore, it is not surprising that these two hexoses are also perfectly absorbed by the cells of many plants [ 125 , 133 , 140 ], including tobacco [ 126 , 135 , 141 , 142 , 143 ] and A. thaliana [ 61 , 144 , 145 ]. In some cases, the combined presence of both of these sugars in the incubation medium gave a better biomass growth compared to those with their individual use [ 84 ].…”
Section: Organic Substratesmentioning
confidence: 99%
See 1 more Smart Citation